PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 005 RAJA BEJAMU KECAMATAN SINABOI - Razali '; Syahrilfuddin '; Zariul Antosa Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem back groud of this research is the lower of the science result. This case can be seen from the science result of students’ test. That is 57,5 and also from the result of totally passing grade the student reach, Among 20 students, only 6 students who get good passing grade, or only 30 % who succed in getting passing grade. The passing grade that has been ditermind by The school is 6.5. The problem of this research is “can the cooperative learning modelling type STAD increase the result of study science to the thira year students of the state secondary school of 005 Raja Bejamu Kecamatan Sinaboi Kabupaten Rokan Hilir. The hypothesis used in this reseach is that “By using cooperative learning modelling type STAD, Can improve the result of study science to the third year students of the 005 scondary school Raja Bejamu, Kecamatan Sinaboi, Kabupaten Rokan Hilir. This research is conducted within 2 cilcius in 6 meeting times. Which consists of 4 material persen tations and 2 formative test. Times after the data has been collected, Then it will be ana lized. The result of the analyzed have been typed as the following below. The basic score is 57,5, become higher into 64,5 or get increa sing 7 point. The second test / exam is 78, get higher 64,5 or get incereasing, 13,5 point. This classically, from the basic score to the second form tive exam (UH II) is higher, That is 20,5 point. The teacher activity anda the students activity are also influene by using this cooperative learning modelling. The second teacher activity is 66 % higher the the first. Techer activity that is 58 %. The third teacher activity II 75 % and from the fifth is 91 % higher that Teacher activity that is 75 %. The first students’s activity is 50 5, will be higher in the second students activity that is 58 %, form the second student meeting willy get higher on the third meeting, that is 70 %, form the forth to the fifth meeting get highet become 83 %.this, the writer can conclude that by using the cooperative learning modelling type STAD can increase the result of study science to the third year students of the 005 state secondary school Raja Bejamu, Kecamatan Sinaboi, Kabupaten Rokan Hilir. Keyword: Cooperative type STAD, The result of IPA